Psychometric evaluation of the Nurse Competence Scale: A cross-sectional study - Phanida Juntasopeepun (2019)
© 2019 John Wiley & Sons Australia, Ltd Measuring nurses' competence for practice is critical for quality and safety improvement in nursing care and patient outcomes. While the Nurse Competence Scale is a widely used international measure of the generic nursing competence of nurses in various career stages, it has not been used in Thailand. This study involved the forward–backward translation of the scale into Thai and evaluation of its psychometric properties with 571 nurses at one public and one private hospital in Chiang Mai, Thailand. Participants also completed a demographic form. The content validity analysis revealed that the item-level content validity index (I-CVI) was.90, and the scale-level content validity index (S-CVI/Average) was.91. The principal component analysis with varimax rotation demonstrated that the six factor structure accounted for 58.45% of the total variance. The Mann–Whitney U-test showed a significant difference between low and high work experience groups for all six factors, providing further support for the scale's construct validity. The reliability analysis showed an acceptable level of Cronbach's alphas in six factors ranging from.82 to.88. In conclusion, the Thai version demonstrated promising psychometric properties, but requires further testing with nurses in different settings before use in practice.